A clinical audit of hysteroscopy in a tertiary care teaching. What challenges did we face? - Mundkur, Anjali; Adiga, Prashanth K.; Kumar, Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of the study was to evaluate indications, operative findings and complications in patients undergoing hysteroscopy. Methods: The data of all patients who underwent hysteroscopy in the department of obstetrics and gynecology in a tertiary care teaching hospital were included retrospectively from November 2017 to October 2018. Results: There were 59 patients who had hysteroscopy for various indications. Twelve patients and forty-seven patients were subjected to diagnostic and operative hysteroscopy respectively. Indications for diagnostic hysteroscopy were for postmenopausal bleed (3), carcinoma of the breast on tamoxifen with bleeding PV (3), recurrent implantation failure (6). Operative hysteroscopy was performed for endometrial polyp (30), myomectomy (9), septal resection (7), copper T removal (1). Complications of hysteroscopy were: media efflux and poor visualization in 10 (17%), minor hemorrhage (9) 15.1%, perforation 2 (3.3%). Minor hemorrhage was managed with tranexamic acid. The perforation in two patients happened during the dilatation of the cervix with metal dilators. Conclusions: One of the major challenges encountered was the efflux of the distension media due to excessive cervical dilatation, which did not provide satisfactory hysteroscopic view. Another complication was perforation during cervical dilatation using Hegars dilator. Use of misoprostol and the use of small sheath hysteroscopes have minimized the need for cervical dilatation.